Localizing the sustainable development goals in smart and sustainable cities: how can citizen-generated data support the local monitoring of SDGs? A case study of the Brussels Capital Region - Borghys, Koen; Vandercruysse, Laurens; Veeckman, Carina; Temmerman, Laura; Heyman, Rob (Frontiers in Environmental Science, 2024)
The Sustainable Development Goals (SDGs) serve as the global reference framework for sustainable development endeavors. However, traditional data sources, including official statistics, fall short in effectively measuring SDG performance, due to substantial gaps in the availability of reliable, timely, actionable, disaggregated, and accessible information for policy formulation. This research explores the potential of citizen generated data to enhance local environmental in the Brussels Capital Region.Employing a qualitative approach, the study first defines and maps essential characteristics of citizengenerated data for inclusion in environmental SDG monitoring. Subsequently, expert interviews refine these characteristics and explore design requirements tailored to the Brussels Capital Region. The research culminates in a framework linking essential citizen-generated data characteristics to design requirements, ensuring data suitability for local environmental SDG monitoring. This framework advances the existing literature by specifically addressing local environmental SDG monitoring through citizen-generated data. It offers practical insights for local stakeholders, particularly policy makers, aiming to overcome barriers to the uptake of citizen-generated data and ultimately enhances environmental SDG monitoring in the Brussels Capital Region. The framework's applicability in other regions or for non-environmental SDG indicators remains a potential avenue for future research. SDGs remains a global agenda with an implicit focus on the national level. Consisting of a policy framework endorsed by all 193 member states of the United Nations (UN) and are set to be achieved by 2030. Currently, there is an ongoing process of localization facilitated by subnational actors, i.e., regional, and local entities (Greene & Meixell, 2017;Oosterhof, 2018).